2021
DOI: 10.3390/life11050369
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Progression Associated with Modifications in Calcium Signaling in Human Lens Epithelia as Studied by Mechanical Stimulation

Abstract: Ca2+ homeostasis and signaling disturbances are associated with lens pathophysiology and are involved in cataract formation. Here, we explored the spatiotemporal changes in Ca2+ signaling in lens epithelial cells (LECs) upon local mechanical stimulation, to better understand the LECs’ intercellular communication and its association with cataractogenesis. We were interested in if the progression of the cataract affects the Ca2+ signaling and if modifications of the Ca2+ homeostasis in LECs are associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Multicellular recordings of membrane potential or intracellular calcium concentration are typically used as input signals. Network principles have thus been used to elucidate the connectivity patterns in neurons ( 40 44 ), astrocytes ( 45 ), pituitary endocrine cells ( 46 , 47 ), lens epithelium cells ( 48 , 49 ), hepatocytes ( 50 ), mammary epithelium cells ( 51 ), endothelial cells ( 52 ), and pancreatic acinar cells ( 53 ). Network analyses were introduced to the islet community a decade ago and are increasingly seen as a valuable tool to examine and quantify collective activity patterns in the pancreatic islets of Langerhans ( 18 , 54 69 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multicellular recordings of membrane potential or intracellular calcium concentration are typically used as input signals. Network principles have thus been used to elucidate the connectivity patterns in neurons ( 40 44 ), astrocytes ( 45 ), pituitary endocrine cells ( 46 , 47 ), lens epithelium cells ( 48 , 49 ), hepatocytes ( 50 ), mammary epithelium cells ( 51 ), endothelial cells ( 52 ), and pancreatic acinar cells ( 53 ). Network analyses were introduced to the islet community a decade ago and are increasingly seen as a valuable tool to examine and quantify collective activity patterns in the pancreatic islets of Langerhans ( 18 , 54 69 ).…”
Section: Introductionmentioning
confidence: 99%
“…The following consequences were observed: crystal fiber swelling, rupture, crystal protein denaturation, decomposition and caused cataract[ 13 , 14 ]. Disturbed calcium homeostasis can cause lens opacity through related mechanisms, such as abnormal differentiation of lens epithelial cells (LECs) into fibrocytes, increased migration of LECs into the posterior capsule, lens protein clustering and calcium channel inactivation[ 15 - 17 ]. In this case, we observed that the lens presented bilateral and symmetrical punctate opacity in the posterior subcapsular cortex together with radial opacity in the peripheral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the metabolism of the lens epithelium caused by oxidative stress impair Ca 2 + homeostasis and signaling. This event leads to calcium accumulation and calpain protease activation, which finally results in proteolytic processing of the β‐crystallins and lens opacification (Gosak et al, 2021; Maddirala et al, 2017; Tewari et al, 2019). Recent studies have indicated that the application of compounds with antioxidant properties can prevent oxidation‐related cataractogenesis (Maddirala et al, 2017; Tsai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%